Characterisation of an Elastomer for Noise and Vibration Insulation in Lightweight Timber Buildings. Issue 4 (December 2014) - Negreira, Juan; Austrell, Per-Erik; Flodén, Ola; Bard, Delphine
Regulations regarding impact and airborne sound insulation for lightweight timber constructions have become increasingly stringent due in particular to complaints by inhabitants. Accordingly, some building techniques frequently use elastomers at junctions so as to reduce low frequency noise. Development of accurate predictive tools (involving exact material properties) by using numerical methods such as the finite element (FE) method is needed in tackling flanking transmission problems during the design phase of buildings. The present research concerns the characterisation of an elastomer, presenting an accurate method for extracting its material properties from the manufacturer's data sheet (properties there being often linked to such structural effects as shape factors and boundary conditions of samples and tests). The properties were extracted by comparing results obtained by analytical calculations, FE simulations, and mechanical testing, separating geometry and material dependence and ultimately serving as input to commercial FE software for setting up the aforementioned prediction tools.